2004
DOI: 10.1177/070674370404900803
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Treating Problem Gambling: Empirical Status and Promising Trends

Abstract: T his article briefly describes the major pharmacologic and psychological treatment modalities for problem gambling and establishes their relative efficacy. We emphasize controlled research for gambling treatment, consistent with the American Psychological Association recommendations regarding empirically validated treatments (EVT; 1,2). These criteria define the conditions that should be met when deciding whether a treatment has been empirically validated. They require that interventions be tested in randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 76 publications
2
85
0
4
Order By: Relevance
“…Cognitive-behavioral therapy is currently considered the most efficient method of treatment for gambling disorder; this type of therapy postulates the fact that the irrational thoughts tied to the ability of a person to control the game and predict the win represent the main factors which determine the development and the maintenance of this pathology [39][40][41][42][43][44][45].…”
Section: Treating Gambling Disordermentioning
confidence: 99%
“…Cognitive-behavioral therapy is currently considered the most efficient method of treatment for gambling disorder; this type of therapy postulates the fact that the irrational thoughts tied to the ability of a person to control the game and predict the win represent the main factors which determine the development and the maintenance of this pathology [39][40][41][42][43][44][45].…”
Section: Treating Gambling Disordermentioning
confidence: 99%
“…Cognitive distortions, or beliefs and practices held and used by gamblers to help determine or procure a gambling outcome, are reported to play a fundamental role in the maintenance and development of gambling problems (Cunningham et al, 2014;Fortune & Goodie, 2012;Toneatto & Millar, 2004). Research on problem versus social gamblers demonstrates the greater likelihood of those experiencing problem gambling endorsing such beliefs (Joukhador et al, 2004;Myrseth et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of these beliefs in understanding gambling behaviour is well demonstrated by the wealth of research on them and by the published instruments used to measure distortions in gamblers (Goodie & Fortune, 2013). A growing area of interest in the gambling literature is specification by gambling subtype, including by game type (Raylu & Oei, 2002;Toneatto & Millar, 2004;Toneatto, Turner, Zack, Farvolden, & Bagby, 2007). Important game type differences in cognitive biases have been alluded to (Czerny, Koenig, & Turner, 2008), although little research has focused on this area.…”
Section: Introductionmentioning
confidence: 99%
“…15 A literature review investigating the use of CBT for problem gambling also found that group and individual CBT is helpful in reducing gambling behaviour, severity and psychological distress. 16 Other treatments for which there is some evidence are motivational enhancement therapies, brief interventions, self-help programmes and Gambler Anonymous.…”
Section: Treatmentmentioning
confidence: 99%